Pengaruh Promosi Terhadap Kepuasan Pelanggan di Toko Aleea Shopid Kebumen - Wakhid Yuliyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Aleea Shopid Shop one of the shops in Kebumen that was growing in the field of sales of women's equipment. This study aimed to determine the effect of promotion on customer satisfaction on Shop Aleea Shopid Kebumen. Data collection methods used were questionnaire method, observation, unstructured interview and literature study. The analytical methods used were validity test, reliability test, classical assumption test, simple linear regression analysis, and t test. The preparation used qualitative method with quantitative approach. The result of analysis shows that there was a positive and significant influence between promotion on customer satisfaction on Aleea Shopid Shop Kebumen with prosentase 40,7%. Significant value for the effect of X (promotion) on Y (customer satisfaction) was 0.000 < from 0.05 and t value of 4.763 > from 2.037. The problems that exist on Aleea Store was the lack of promotion done to market their products. The solution was to evaluate and determine the promotion that will be used in accordance with targeted targeted market to attract consumers